A historical welfare analysis of Social Security: Whom did the program benefit?. Issue 4 (2nd December 2019) - Peterman, William B.; Sommer, Kamila
Abstract : A well‐established result in the literature is that Social Security reduces steady state welfare in a standard life cycle model. However, less is known about the historical quantitative effects of the program on agents who were alive when the program was adopted. In a computational life cycle model that simulates the Great Depression and the enactment of Social Security, this paper quantifies the welfare effects of the program's enactment on the cohorts of agents who experienced it. In contrast to the standard steady state results, we find that the adoption of the original Social Security generally improved these cohorts' welfare, in part because these cohorts received far more benefits relative to their contributions than they would have received if they lived their entire life in the steady state with Social Security. Moreover, the negative general equilibrium welfare effect of Social Security associated with capital crowd‐out was reduced during the transition, because it took many periods for agents to adjust their savings levels in response to the program's adoption. The positive welfare effect experienced by these transitional agents offers one explanation for why the program that may reduce welfare in the steady state was originally adopted.